Efficacy of finafloxacin in a murine model of inhalational glanders - Barnes, Kay B.; Bayliss, Marc; Davies, Carwyn; Richards, Mark I.; Laws, Thomas R.; Vente, Andreas; Harding, Sarah V. (Frontiers in Microbiology, 2022)
Burkholderia mallei, the causative agent of glanders, is principally a disease of equines, although it can also infect humans and is categorized by the U.S. Centers for Disease Control and Prevention as a category B biological agent. Human cases of glanders are rare and thus there is limited information on treatment. It is therefore recommended that cases are treated with the same therapies as used for melioidosis, which for prophylaxis, is co-trimoxazole (trimethoprim/sulfamethoxazole) or co-amoxiclav (amoxicillin/clavulanic acid). In this study, the fluoroquinolone finafloxacin was compared to co-trimoxazole as a post-exposure prophylactic in a murine model of inhalational glanders. BALB/c mice were exposed to an aerosol of B. mallei followed by treatment with co-trimoxazole or finafloxacin initiated at 24 h post-challenge and continued for 14 days. Survival at the end of the study was 55% or 70% for mice treated with finafloxacin or co-trimoxazole, respectively, however, this difference was not significant. However, finafloxacin was more effective than co-trimoxazole in controlling bacterial load within tissues and demonstrating clearance in the liver, lung and spleen following 14 days of therapy. In summary, finafloxacin should be considered as a promising alternative treatment following exposure to B. mallei.